Association between antibiotics and dementia risk: A retrospective cohort study - Kim, Minseo; Park, Sun Jae; Choi, Seulggie; Chang, Jooyoung; Kim, Sung Min; Jeong, Seogsong; Park, Young Jun; Lee, Gyeongsil; Son, Joung Sik; Ahn, Joseph C.; Park, Sang Min (Frontiers in Pharmacology, 2022)
Background: The possible relation between antibiotic exposure and the alteration of gut microbiota, which may affect dementia risk, has been revealed. However, the association between antibiotics and dementia incidence has rarely been studied. We aimed to determine the association between antibiotic exposure and the risk of dementia. Methods: This population-based retrospective cohort study used data from the National Health Insurance Service-Health Screening Cohort (NHIS-HEALS) in South Korea. Exposure was the cumulative days of antibiotic prescription from 2002 to 2005. Newly diagnosed overall dementia, Alzheimer’s disease (AD), and vascular dementia (VD) were identified based on diagnostic codes and prescriptions for dementia-related drugs. The follow-up investigation was carried out from 1 January 2006 to 31 December 2013. The Cox proportional hazards regression was used to assess the association between cumulative antibiotic prescription days and dementia incidence. Results: A total of 313,161 participants were analyzed in this study. Compared to antibiotic non-users, the participants who used antibiotics for 91 or more days had an increased risk of overall dementia [adjusted hazard ratio (aHR), 1.44; 95% confidence interval (CI), 1.19–1.74], AD (aHR, 1.46; 95% CI, 1.17–1.81), and VD (aHR, 1.38; 95% CI, 0.83–2.30). Those who used five or more antibiotic classes had higher risks of overall dementia (aHR, 1.28; 95% CI, 1.00–1.66) and AD (aHR, 1.34; 95% CI, 1.00–1.78) than antibiotic non-users. Conclusion: Antibiotic exposure may increase the risk of dementia in a cumulative duration-dependent manner among adult participants. Future studies are needed to assess the causality between the long-term prescription of antibiotics and dementia risk.